2009
DOI: 10.1051/0004-6361/200911833
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear interaction gamma-ray lines from the Galactic center region

Abstract: Aims. The accretion of stars onto the central supermassive black hole at the center of the Milky Way is predicted to generate large fluxes of subrelativistic ions in the Galactic center region. We analyze the intensity, shape, and spatial distribution of de-excitation gamma-ray lines produced by nuclear interactions of these energetic particles with the ambient medium. Methods. We first estimated the amount and mean kinetic energy of particles released from the central black hole during star disruption. We the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…By matching with the observed flux in the knee region we find that the conversion efficiency from shocks in the bubble to CRs is about 10%, which is quite consistent with numerical simulations. Other input parameters in this model, such as the capture timescale τ cap ∼ 3 × 10 4 yr, the mean rate of energy releasė W ∼ 3 × 10 40 erg s −1 per capture, and the injected wind speed u ∼ 10 8 cm s −1 , have been estimated and used in other observed phenomena in the GC (e.g., Cheng et al 2006Cheng et al , 2007Dogiel et al 2009aDogiel et al , 2009bDogiel et al , 2009cDogiel et al , 2011.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…By matching with the observed flux in the knee region we find that the conversion efficiency from shocks in the bubble to CRs is about 10%, which is quite consistent with numerical simulations. Other input parameters in this model, such as the capture timescale τ cap ∼ 3 × 10 4 yr, the mean rate of energy releasė W ∼ 3 × 10 40 erg s −1 per capture, and the injected wind speed u ∼ 10 8 cm s −1 , have been estimated and used in other observed phenomena in the GC (e.g., Cheng et al 2006Cheng et al , 2007Dogiel et al 2009aDogiel et al , 2009bDogiel et al , 2009cDogiel et al , 2011.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In a series of papers (Cheng et al 2006(Cheng et al , 2007Dogiel et al 2009aDogiel et al , 2009bDogiel et al , 2009cDogiel et al , 2011, we developed a model of energy release in the GC due to star accretion onto the central black hole for the interpretation of X-ray and gamma-ray emission from the GC. Our goal was to explain these observational data in the framework of a single model.…”
Section: Introductionmentioning
confidence: 99%
“…We see that the required proton luminosity in the GC region, ≤ 10 40 erg s −1 , seems to be quite reasonable if supplied by SNs in the GC (see Crocker et al, 2011). As Cheng et al (2007Cheng et al ( , 2011 and Dogiel et al (2009c) showed, this luminosity of subrelativistic and relativistic CRs in the GC can also be provided by processes of star accretion onto the central black hole, though as we mentioned these estimates cannot be considered as reliable.…”
Section: 4 Kev Emission From Sgr B2 Produced By Subrelativistic Promentioning
confidence: 78%
“…As a result, a flux of subrelativistic protons is ejected from the GC, which heats the central region with the necessary power. These protons can also produce 6.4 keV line emission from molecular clouds which is, however, stationary because the lifetime of these protons τ p ∼ 10 7 yr [3] is much longer than the characteristic time of star capture by the central black hole (τ c ∼ 10 5 yr) [1].…”
Section: Introductionmentioning
confidence: 99%